Trans Life and the Catholic Church Today. Edited by Nicolete Burbach and Lisa Sowle Cahill. New York: T&T Clark, 2024. x + 369 pages. $133.00. - Jack, Jason Steidl (Horizons, 2025)
Trans Life and the Catholic Church Today. Edited by Nicolete Burbach and Lisa Sowle Cahill. New York: T&T Clark, 2024. x + 369 pages. $133.00. - Volume 52 Issue 2